(3cTa GdeTcd ef eSGfjO GdUMGHIs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3Ydi Hf CHj HcQ GdcGJH s)
(3ChdgG (B:s
(3acja GSJMd bJdge hSHi PQGQjge Ke cjb bGd dh efYehfi Ch YbGdkG hGdYfGb hGdYbGd dGjDNPGf ai GdRcGI s
(3BNQgG (B:s
(3hcPdc bhdg (B(( (3hGUHQ faSc eY GdPjf jOYhf QHge HGdZOGg hGdYTQi (B) (3BNQ GdLRA GdChdi jJdhg Gf TGA Gddg ai GdPi jdjg cTa GdeTcd ef eSfO SeQI Hf LfOH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1495s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs